Sustained Inattentional Blindness Does Not Always Decrease With Age - Zhang, Hui; Yan, Congcong; Zhang, Xingli; Fang, Jie (Frontiers in Psychology, 2018)
Children are usually missing some additional information when they focus on objects or events. It is a common phenomenon and it is termed as inattentional blindness. In order to explore the age-related degree of this phenomenon, we applied Motion Task to study the developmental differences of inattentional blindness. Some 7-to-14-year-old children and adults were employed to take part in Experiment 1. The results showed that there was no significant developmental difference in sustained inattentional blindness. Considering young children’s performance on the primary task was not quite good, we hypothesized that the difficulty of the primary task may contribute to the negative finding. Therefore, we decreased the difficulty of the primary task in Experiment 2. Finally, the developmental difference on inattentional blindness rates was still absent. Overall, current results implied that the ability to detect the moving unexpected stimuli doesn’t always increase with age. Age difference of inattentional blindness seems highly dependent on tasks.